A radiation-hardened Sense-Switch pFLASH cell for FPGA. (December 2019) - Liu, Guozhu; Li, Bing; Wei, Jinghe; Hong, Genshen; Yu, Zongguang; Wang, Haibin
Abstract: In this paper, a radiation-hardened Sense-Switch pFLASH cell is presented. It employs a programming/erasing transistor (T1 ) as well as a signal transmission transistor (T2 ). They share the common floating and controlling gates. The proposed cell with the total ionizing dose (TID) tolerance of more than 50 Krad(Si) is prepared successfully based on 0.13 μm eFlash technology. Firstly, the "ON/OFF" functions are realized by both the band-to-band tunneling induce hot electron (BBHE) and the Fowler-Nordheim (FN) tunneling mechanisms. Secondly, the "ON/OFF" states are characterized, and the endurance and the TID effects are also studied. Finally, the experimental results show that the mean value of the T1 /T2 threshold window and uniformity of them are approximately 10 V and 3.3%, respectively. Under the working voltage of −1.5 V, the leakage current of T2 at OFF state is as low as 1 pA/μm, and the average driving current of T2 at ON state is around 126.8 μA/μm, and the uniformity of driving current can reach 6.31%. Meanwhile, the number of program and erase cycles can be up to 10, 000 times. Therefore, the Sense-Switch pFLASH cell, which has low leakage, high endurance, better TID tolerance and other excellent characteristics, can meet the basic switch core requirements of radiation-hardened programmable logic devices. Highlights: A Sense-Switch pFLASH cell for radiation-hardened reconfiguration FPGA is proposed and designed with the "ON/OFF" functions using BBHE programming and FN erasing. The Sense-Switch pFLASH cell employs a programming/erasing transistor (T1 ) as well as a signal transmission transistor (T2 ), and they share the common floating and controlling gates. The experimental results show that the T1 /T2 threshold window and uniformity of them are approximately 10V and 3.3%, respectively. Under the working voltage of -1.5V, the leakage current of T2 at OFF state is as low as 1 pA/μm, and the average driving current at ON state is around 126.8μA/μm. Besides, it also has a TID tolerance up to >50 Krad(Si). The Sense-Switch pFLASH cell can meet the basic switch core requirements of radiation-hardened programmable logic devices.